AN ANALYSIS ON THE STUDENTS’ ATTITUDE TOWARDS THE USE OF GOOGLE CLASSROOM IN ENGLISH LEARNING: A Descriptive Study at the Eighth Grade of SMPN 27 Surakarta 2022 / 2023 Academic Year - Etika Nanda Aryanti; Sumardiono Sumardiono (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2022)
This research aimed to find out the students’ attitude towards the use of Google Classroom in English learning at the Eighth Grade of SMPN 27 Surakarta 2022 / 2023 Academic Year. This study was conducted in the eighth grade of SMPN 27 Surakarta 2022 / 2023 Academic Year. The researchers utilize descriptive research which was conducted from June until July. The students of VIII-E were the subject of this research with totally of 30 students. Questionnaires to the students, interviewing the English teacher, and observing the class were the data collected by the researchers. To analyze the data, the researchers used qualitative data. The result of the research showed that the use of Google Classroom in learning English provides advantages and disadvantages for students. Using Google Classroom is quite effective for use in online learning. However, the use of Google Classroom in learning English is not good if it is applied continuously because it will make students difficult to learn English and improve their English skills. Most of the students also disagree that using Google Classroom is more flexible than face-to-face learning. Could be concluded that learning English using Google Classroom is quite helpful in learning during the pandemic, but the use of Google Classroom is not recommended to be used continuously in learning English. Keywords: Students’ Attitude, Google Classroom, English Learning